(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Although talent development is increasingly needed in organizations, there is skepticism about its notion in blueprint and reality. This paper probes and extends better understanding into the disparity on the dissimilarities of the notion, meanings and approach to talent development. It also examines the range of tools available to organizations for development. Gaining inferences from a series of research papers, it revealed that talent development is an important constituent of the complete mechanism of talent management. The study underlined why talent development has proved crucial to the success of an organization, whether in prosperity or adversity. The restrictions faced by organizations in the implementation of TD strategy have also been discussed. Though the study is exclusively qualitative in its essence; it highlights avenues for future studies. This study will help training professionals in dealing with certain problems and challenges that lead to the management and development of talent at work.